Kaji Banding Kesadaran Metakognitif Antara Para Siswa Dan Siswi Kelas Tinggi SD Di Bumi Raya, Morowali - Mufidah, Asmaul; Aloysius, Duran Corebima; Surjati, Endang (Direktorat Pascasarjana Universitas PGRI Kanjuruhan Malang, 2023)
Student competency development will be good, one of them is if student have metacognitive awareness. This reseach aims to determine: 1) student’s meta-cognitive awareness between high classes (4th, 5th, 6th) of elementary school in Bumi Raya Morowali; 2) metacognitive awareness between male and female students in high class of elementary school; 3) metacognitive awareness of male and female students between high classes in elementary school. This research is a comparative survey research. The instrument of the research is used MAI-Sraw and Denisson (1994) that modified suit for elemantary school students’s literacy skill. The respondents who have been involved are 134 students, respondents were selected using probability sampling technique. Also use inferencial parametric statistic (two way anova). This research results that: 1) Student’s metacognitive awareness of 4th grade is different, possessed lowest level than 5th grade and 6th grade. Student’s metacognitive awareness of 5th grade and 6th grade is not different each other. First concluded analysis that student’s metacognitive awareness between high classes of elementary school in Bumi Raya Morowali is different. 2) The metacognitive awareness between male and female students overall is not different. 3) Interaction between level of grade and gender on student’s metacognitive awareness are: the metacognitive awareness between male and female students of 4th grade also male students of 5th grade is not different; the metacognitive awareness between male and female students of 4th grade is different from male students of 6th grade, female students of 6th grade and female students of 5th grade; than the metacognitive awareness of male and female students of 5th grade with the metacognitive awareness of male and female students of 6th grade is not different. The recommendations for the next research are to apply longitudinal research and to add the the variabel’s research in order to get gradual describtion of student’s metacognitive awareness.